The problems and perspectives of uninterrupted education in the field of physical training and sport. - Kurtova G.U (Kharkov National Pedagogical University, 2011)
Scientific investigations in the direction of uninterrupted pedagogical education in the field of physical culture and sport are examined. The analysis of Russian and Ukrainian scientists publications concerning different aspects of educational system function are given. The ways of pedagogical skills in the preparation of high qualified specialists are observed. It is proved, that the problems of uninterrupted education in modern educational expanse are made sense of now. The main aspects of uninterrupted education essence are marked out: compensational, formal and sociocultural.